Manejo agronómico del cultivo de camote (Ipomoea batatas, Lamark 1793), en el Ecuador - Burgos Jaramillo, Allison Briggette (2023)
In Ecuador, the cultivation of sweet potato is having importance at the national level, its consumption and production is carried out in different areas of the Coast, Sierra and Amazonia regions. The agronomic management practices of the sweet potato crop that lead to excellent production and good quality, however, due to poor agronomic management, the sweet potato crop varieties have not been able to demonstrate their true yield potential and there is no good modernization in the conventional cultivation system, either in the plantation or in the harvest. There are not many improved sweet potato varieties in the country, however, INIAP has been carrying out a selection process for improved varieties. The Pichilingue Tropical Experimental Station has a germplasm bank of 392 species collected in 18 provinces of the country, of which 64% correspond to the Coast, 19% to the East, and 17% to the Sierra. The research techniques used in this investigative work are exploratory and explanatory by means of which it has been obtained as a result that the success of good sweet potato production is using cuttings obtained from the tip of the stems of the plant. In addition, the most effective method for weed control is using plastic covers. On the other hand, drip irrigation is the one that is used the least but the one that provides the greatest positive results in production. Concluding that the main challenges facing sweet potato cultivation in Ecuador are the lack of technical knowledge of farmers and the application of agricultural techniques to improve the management of this crop.